Faustian bargains: Short‐term and long‐term contingencies in phylogeny, ontogeny, and sociogeny. Issue 1 (7th December 2022) - Stahlman, W. David; Catania, A. Charles
Abstract : Rachlin's interpretations of self‐control depend on the short‐term versus the long‐term consequences of behavior. Sometimes these effects support each other (typing an abstract produces a written product now and is later read by others). Sometimes they conflict (procrastination now is incompatible with finishing the abstract by deadline). We usually reserve the language of self‐control for human cases where long‐term consequences are chosen over short‐term ones. Rachlin made this distinction salient in ontogeny, but it also applies to selection in phylogeny (Darwinian evolution) and sociogeny (behavior passed from one organism to another). Our account examines relations between short‐term and long‐term consequences at each level of selection. For example, sexual selection has adaptive, short‐term mating consequences but may drive species to extreme specializations that jeopardize long‐term survival. In sociogeny, as in the Tragedy of the Commons, group members may get immediate economic benefits from exploiting resources but exhaust those resources over the long term. Whatever the level, when short‐term and long‐term consequences have opposing effects, adaptive behavior may depend on whether temporally extended contingencies exert more control than more immediate benefits.